2023
DOI: 10.3892/ijmm.2023.5291
|View full text |Cite
|
Sign up to set email alerts
|

Role of CELF2 in ferroptosis: Potential targets for cancer therapy (Review)

Abstract: Ferroptosis is a novel form of regulated cellular necrosis that plays a critical role in promoting cancer progression and developing drug resistance. The main characteristic of ferroptosis is iron-dependent lipid peroxidation caused by excess intracellular levels of reactive oxygen species. CUGBP ELAV-like family number 2 (CELF2) is an RNA-binding protein that is downregulated in various types of cancer and is associated with poor patient prognoses. CELF2 can directly bind mRNA to a variety of ferroptosis cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 197 publications
(248 reference statements)
0
3
0
Order By: Relevance
“…CELF2 is a critical tumor suppressor in a variety of tumors that inhibits proliferation and promotes apoptosis of cancer cells (41)(42)(43). Moreover, CELF2 can directly bind mRNAs of ferroptosis regulators (13). In this study, we found that CELF2 expression was elevated in both AKI models, but it was decreased by miR-208a-3p.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…CELF2 is a critical tumor suppressor in a variety of tumors that inhibits proliferation and promotes apoptosis of cancer cells (41)(42)(43). Moreover, CELF2 can directly bind mRNAs of ferroptosis regulators (13). In this study, we found that CELF2 expression was elevated in both AKI models, but it was decreased by miR-208a-3p.…”
Section: Discussionmentioning
confidence: 52%
“…Apoptosis is an important form of renal tubular epithelial cell death (40). Ferroptosis is a new regulated cell death program (13). Inhibition of ferroptosis has been found to be a promising therapeutic strategy for the protection of tubular epithelial cells against I/R injury (9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation